2015
DOI: 10.1128/mbio.00621-15
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of the Endophyte Burkholderia phytofirmans PsJN Indicates Sensing of the Plant Environment and Drought Stress

Abstract: It is widely accepted that bacterial endophytes actively colonize plants, interact with their host, and frequently show beneficial effects on plant growth and health. However, the mechanisms of plant-endophyte communication and bacterial adaption to the plant environment are still poorly understood. Here, whole-transcriptome sequencing of B. phytofirmans PsJN colonizing potato (Solanum tuberosum L.) plants was used to analyze in planta gene activity and the response of strain PsJN to plant stress. The transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 50 publications
3
93
0
2
Order By: Relevance
“…The probe and primers were designed in a previous study (Sheibani-Tezerji et al, 2015) to match the gene for transcription termination factor rho (Bphyt_1824) in the genome of strain PsJN. qPCR reactions contained (10 μl total volume): 1x SsoFast Probes, 0.5 μM of each primer, 0.35 μM probe, and 5–100 ng DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The probe and primers were designed in a previous study (Sheibani-Tezerji et al, 2015) to match the gene for transcription termination factor rho (Bphyt_1824) in the genome of strain PsJN. qPCR reactions contained (10 μl total volume): 1x SsoFast Probes, 0.5 μM of each primer, 0.35 μM probe, and 5–100 ng DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterium itself is also active inside plant. More than 60% of all genes encoded on the genome were expressed in P. phytofirmans PsJN during endophytic colonization of potato plants and gene expression pattern changed in response to host plant drought stress (Sheibani-Tezerji et al, 2015). In shoots of Arabidopsis thaliana strain PsJN expresses genes related to iron storage and transport, which resulted in enhanced iron uptake and accumulation in the host plant (Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that individual taxa have evolved specific strategies to successfully move to favorable locations and persist in these environments. However, transcripts related to motility were underrepresented in a Burkholderia strain endophytic in potato plants, indicating that motility might no longer be needed once cells have attached to or entered a plant tissue (117). Similarly, analysis of the transcriptome of a leaf-pathogenic Pseudomonas strain revealed high expression of genes related to motility during epiphytic growth, whereas expression was strongly reduced when the bacteria were colonizing the apoplast (153).…”
Section: The Plant Microbiome: Functional Adaptation To the Plant Envmentioning
confidence: 99%
“…Indeed, stress response was identified as a significantly enriched functional category in grapevine rhizosphere metagenomes compared with surrounding bulk soil (157). Furthermore, transcriptional profiling of endophytic Burkholderia of potato plants exposed to drought stress indicated that endophytes are affected by environmental influences, and upregulation of several extracytoplasmic function (ECF) sigma factors potentially involved in stress resistance was observed (117). Besides abiotic stresses, plant microbiota are exposed to biotic stresses and antimicrobial compounds of both plant and microbial origin.…”
Section: The Plant Microbiome: Functional Adaptation To the Plant Envmentioning
confidence: 99%
“…These three genera have also been detected as endophytes in the roots of Mexican husk tomato plants (Physalis ixocarpa Brot.) by Márquez-Santacruz et al (2010), and as regular microbiota in many other plant hosts (Li et al, 2015;Ludwig-Müller, 2015;Sheibani-Tezerji et al, 2015).…”
Section: Discussionmentioning
confidence: 99%